Process Studies on the W-C-Ti System Using a High-Throughput Laser-Based Additive Manufacturing Approach - Tim Schubert; Christiana Malchus; Julian Schurr; Emanuel Wengenmayr; Timo Bernthaler; Gerhard Schneider (Metals, 2025)
Conventional WC-Co hard metals have proven to be difficult to manufacture by means of laser powder bed fusion (PBF-LB), resulting in residual pores, crack formation, foreign phase formation, and the inhomogeneous growth of the carbide phase. Alternative compositions such as the W-C-Ti system presented in this study need to be investigated. Through the employment of a high-throughput screening approach, 11 alloy compositions were investigated to determine the influence of the carbon content and tungsten–titanium ratios on microstructure formation and basic mechanical properties. Two screenings were conducted, with one varying the carbon content (10–35 at.%) and the other adjusting the W/Ti ratios (10:90 to 60:40 at.%). Microstructural analyses using scanning electron microscopy (SEM), X-ray diffraction (XRD), and hardness measurements provided insights into phase formation, grain distribution, and mechanical properties. The results showed that increasing the carbon content significantly enhanced the hardness (from 681 HV (10 at.% C) to 1898 HV (35 at.% C)) due to higher δ-(Ti,W)C1−x carbide phase fractions. Alloys with a higher tungsten content exhibited finer microstructures and an improved crack resistance while maintaining a high hardness (1900–2100 HV). This study identified an alloy with 32.5 at.% W, 32.5 at.% Ti, and 35 at.% C as a promising candidate for further investigation, with properties similar to those of a conventional WC-Co hard metal.